Degradation of dipyrone by electrogenerated H2O2 combined with Fe2+ using a modified gas diffusion electrode - Barros, Willyam R. P.; Borges, Michelle P.; Steter, Juliana R.; Forti, Juliane C. [UNESP]; Rocha, Robson S.; Lanza, Marcos R. V. (Electrochemical Soc Inc, 2014)
The aim of the present study was to investigate the electrochemical degradation of dipyrone in a single compartment electrochemical cell equipped with a gas diffusion electrode (GDE) modified with cobalt (II) phthalocyanine. Degradations were performed under conditions of anodic oxidation (GDE pressurized with N-2) and under conditions promoting the electrogeneration of H2O2 (GDE pressurized with O-2) both in the absence and presence of 1 mmol FeSO4.7H2O (electro-Fenton conditions). The efficiency of the electro-Fenton process was satisfactory at all studied potentials, and achieved a maximum reduction of 67% in electrolyte absorbance at 262 nm after 90 min electrolysis at -0.7 V (vs. Ag/ AgCl). The reduction in dipyrone concentration attained 95% after 90 min of reaction with electrogenerated H2O2 in the absence or presence of Fe2+ ions at all potentials except -0.5 V (vs. Ag/ AgCl). The removal of total organic carbon (TOC) was most efficient under electro-Fenton conditions with a decrease of 54.4% in organic load attained at -0.9 V (vs. Ag/AgCl) and energy consumption (EC) of 270 kWh per kg of TOC removed. (C) 2014 The Electrochemical Society. All rights reserved.